1996
DOI: 10.1046/j.1464-410x.1996.09717.x
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical experience with 5‐aminolevulinic acid for the photodynamic therapy of superficial bladder cancer

Abstract: Objective To report clinical experience with intravesical instillations of 5‐aminolevulinic acid (ALA) for the photodynamic therapy of superficial bladder cancer and to assess any side‐effects of the treatment. Patients and methods Ten patients (six men and four women, mean age 62.3 years, range 42–73) with refractory superficial bladder cancer were treated with photodynamic therapy using 5 g of ALA dissolved in 30 mL sodium bicarbonate instilled intravesically. After a mean retention of 5.1 h, the bladder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
86
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 3 publications
4
86
0
4
Order By: Relevance
“…Confirmed by histopathological examination, we have demonstrated that the fluorescence of PpIX in the urothelium induced by intravesically administered h-ALA correlated significantly with neoplastic lesions and was suitable for the detection of papillary tumours as well as for dysplasia and carcinoma in situ. The 7% rate of false negative responses found in the present study is comparable to the value given by Jichlinski et al in 1997 and slightly higher than that presented by the Munich group (Kriegmair et al, 1996). A total number of 28 biopsies were taken from areas proven to be benign.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Confirmed by histopathological examination, we have demonstrated that the fluorescence of PpIX in the urothelium induced by intravesically administered h-ALA correlated significantly with neoplastic lesions and was suitable for the detection of papillary tumours as well as for dysplasia and carcinoma in situ. The 7% rate of false negative responses found in the present study is comparable to the value given by Jichlinski et al in 1997 and slightly higher than that presented by the Munich group (Kriegmair et al, 1996). A total number of 28 biopsies were taken from areas proven to be benign.…”
Section: Discussionsupporting
confidence: 82%
“…Only five of these samples revealed an enhanced red fluorescence under violet light irradiation, yielding a rate of falsely positive fluorescence findings of 17%. This result seems to be quite small compared to both the results of Kriegmair et al (1996) and Jichlinski et al (1997). But it may be explained by the small number of biopsies taken, or the fact that the fluorescence induced by the long-chain esters was found to be limited to the site of application (Peng et al, 1996), hence no supplementary PpIX build-up from systemic ALA uptake is observed.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Aminolaevulinic acid (ALA) is currently undergoing clinical trials as a means of inducing photosensitization for PDT of bladder (Kriegmair et al, 1996) and skin cancers (Cairnduff et al, 1994). It is well established that photodynamic toxicity using haematoporphyrin derivative (HPD) can be almost completely abolished by hypoxia.…”
mentioning
confidence: 99%